The Role of Sovereign Wealth Funds in Global Managament of Excess Foreign Exchange Reserves - Urban, Dariusz (Comparative Economic Research. Central and Eastern Europe, 2011)
This paper finds evidence that for many countries Sovereign Wealth Funds are the alternative vehicle for management of excess foreign exchange reserves. These funds can be seen as a substitutes for monetary authorities as well as institutional innovations on global financial markets. Sovereign Wealth Funds offer to countries various economic and financial benefits. They facilitate saving intergenerational transfer of proceeds from nonrenewable resources and help reduce cyclical volatility driven by changes in commodity export prices. These state-run funds help to reduce the opportunity cost of reserves holdings due to greater portfolio diversification of reserve-assets and allow countries to accumulate large capital inflow without negative consequences such as exchange rate appreciations, price distortions, liquidity expansion, domestic asset bubbles, financial sector imbalances and inflations. Sovereign Wealth Funds can support domestic economy during the crises as a investors of last resort and stabilize international financial markets by supplying liquidity and reducing market volatility. Sovereign Wealth Funds are likely to continue growing and increase their relative importance in global financial markets.